Microfluidic hydrodynamic trapping for single cell analysis: mechanisms, methods and applications - Vigneswaran, Narayanamurthy; Nagarajan, Sairam; Al'aina Yuhainis, Firus Khan; Fahmi, Samsuri; Sridhar, T. M. (Royal Society of Chemistry, 2017)
The development of hydrodynamic-based microfluidic biochips has been increasing over the years. In this technique, the cells or particles are trapped in a particular region for single cell analysis (SCA) usually without any application of external force fields such as optical, electrical, magnetic or acoustic. There is a need to explore the insights of SCA in the cell's natural state and development of these techniques is highly essential for that study. Researchers have highlighted the vast potential field that needs to be explored to develop biochip devices to suit market/researcher demands. Hydrodynamic microfluidics facilitates the development of passive lab-on-chip applications. This review gives an account of the recent advances in this field, along with their mechanisms, methods and applications.